Study on Cardiovascular Changes in Exercise - Shelja Deswal; Kiran Dahiya; Mridul Yadav; . Beena (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Physical exercise is the most extreme stress that the body encounters during everyday life. During an acute bout of exercise, the body must make rapid and integrated cellular and organ-system adjustments to meet the body’s metabolic, thermal, and fluid demands. Exercise physiology is the study of the physical and chemical events that provide for the conversion of chemical energy to mechanical work. Both the contraction and the relaxation processes in skeletal muscle require energy. The study of exercise physiology uncovers the control processes that are responsible for making energy available to skeletal muscles during acute exercise and for slower adaptations during training. The primary aim of cardiovascular changes in exercise is to supply adequate oxygenated blood to exercising muscle at a rate that meets their metabolic demand. This is achieved by cardiovascular responses. Our objective is to analyse how determinants of cardiac performance operate during exercise.